Spatial distribution of dust–bound trace elements in Pakistan and their implications for human exposure. (June 2016) - Eqani, Syed Ali Musstjab Akber Shah; Kanwal, Ayesha; Bhowmik, Avit Kumar; Sohail, Mohammad; Ullah, Rizwan; Ali, Syeda Maria; Alamdar, Ambreen; Ali, Nadeem; Fasola, Mauro; Shen, Heqing
Abstract: This study aims to assess the spatial patterns of selected dust-borne trace elements alongside the river Indus Pakistan, their relation with anthropogenic and natural sources, and the potential risk posed to human health. The studied elements were found in descending concentrations: Mn, Zn, Pb, Cu, Ni, Cr, Co, and Cd. The Index of Geo-accumulation indicated that pollution of trace metals were higher in lower Indus plains than on mountain areas. In general, the toxic elements Cr, Mn, Co and Ni exhibited altitudinal trends ( P  <  0.05 ). The few exceptions to this trend were the higher values for all studied elements from the northern wet mountainous zone (low lying Himalaya). Spatial PCA/FA highlighted that the sources of different trace elements were zone specific, thus pointing to both geological influences and anthropogenic activities. The Hazard Index for Co and for Mn in children exceeded the value of 1 only in the riverine delta zone and in the southern low lying zone, whereas the Hazard Index for Pb was above the bench mark for both children and adults (with few exceptions) in all regions, thus indicating potential non-carcinogenic health risks. These results will contribute towards the environmental management of trace metal(s) with potential risk for human health throughout Pakistan. Graphical abstract: Highlights: Environmental screening of toxic elements in dust from Pakistan and their health risk. Agricultural and urban areas showed higher metals levels than those of mountainous. Co, Cr, Mn and Ni exhibited altitudinal variability through the studied zones. Sources of trace elements contamination included both natural and anthropogenic. Health Risk due to Pb, Co, and Mn for children and only Pb for adults via dust. Abstract : The presence of dust-borne trace elements throughout Pakistan implies human health risks from exposure to Co, Mn (for children in low elevation regions) and to Pb (for both adults and children throughout the whole country).